2022
DOI: 10.1002/nop2.1441
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses' spiritual care competence and attitude: An online survey

Abstract: Aims This study aimed to assess student nurses' competence and attitude toward spiritual care and analysed the associated factors. Design Cross‐sectional study using an online survey. Methods From April 14 to June 14, 2018, a convenience sample of 938 student nurses were recruited from six schools of Nursing in Hunan Province, China. Data were collected by using the Chinese versions of the Spiritual Care Competence Scale (C‐SCCS) and the Spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The present study found the level of spiritual care competency to be at an average level, which was consistent with the results of other researchers [ 26 , 27 ], although it contrasted with the results of Jafari and Fallahi-Khoshknab [ 28 ] and Nasehi et al [ 29 ]. Kalkim et al reported that the level of spiritual care competency of nursing students in Turkey was not optimal [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study found the level of spiritual care competency to be at an average level, which was consistent with the results of other researchers [ 26 , 27 ], although it contrasted with the results of Jafari and Fallahi-Khoshknab [ 28 ] and Nasehi et al [ 29 ]. Kalkim et al reported that the level of spiritual care competency of nursing students in Turkey was not optimal [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Providing spiritual care requires trained caregivers [ 10 ]. In this sense, knowing what is expected from a caregiver could encourage managers and curriculum planners to promote, through education and training, the spiritual ability and competence of students and caregivers in delivering spiritual care [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have investigated the status and factors affecting nurses' SCC, most have adopted a variable‐centred approach that has focused on testing the relationships of each aspect of SCC with other variables (Guo et al., 2023; Jafari & Fallahi‐Khoshknab, 2021; Wang, Zhao, Zhang, et al., 2020). The person‐centred approach could solve the potential issues of identifying subgroups of nurses with different SCC.…”
Section: Introductionmentioning
confidence: 99%